Role Of Ballistic And Cruise Missiles In International Security - Ghoshal, Debalina (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The book attempts to understand the myriad roles of ballistic and cruise missiles in international security. They are for combat purpose, deterrence, coercive diplomacy and power and prestige of a state. The book also studies missile developments across the world. The book also aims to fathom the various possibilities to reduce the threat from missile systems. Debalina Ghoshal is Non-Resident Fellow at the Council on International Policy, Canada. .
Chapter 1: Theoretical Analysis of Role of Missiles in International Security -- Chapter 2: Technological Aspects of Missiles: Missiles and Warheads -- Chapter 3: Role of Missiles in International Security -- Chapter 4: Why States Acquire Missile Systems -- Chapter 5: Historical and Contemporary Missile Development -- Chapter 6: Survivability of Nuclear Missile Force and Contemporary Debates -- Chapter 7: Can the World Do Without Missiles?.
Keywords: International relations; Security, International; International Relations Theory; International Security Studies